Activated iron-based nanocrystalline alloy and application thereof in degradation of phenol
By immersing the iron-based nanocrystalline alloy in copper sulfate solution to activate it, an activated iron-based nanocrystalline alloy that can efficiently degrade phenol under neutral and alkaline conditions was prepared, which solved the problems of low degradation efficiency of phenol wastewater and large pH adjustment requirements in the prior art, and achieved efficient and low-cost phenol degradation effect.
Patent Information
- Application Number
- CN202411723439.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-04
AI Technical Summary
When treating wastewater containing phenol, the prior art has low degradation efficiency and a large demand for pH adjustment, resulting in high treatment costs and secondary environmental pollution.
By immersing the iron-based nanocrystalline alloy in copper sulfate solution to activate it, an activated iron-based nanocrystalline alloy capable of efficiently degrading phenol under neutral and alkaline conditions was prepared.
It significantly improves the degradation efficiency of phenol, breaks the pH limit of traditional Fenton reactions, reduces the demand for pH adjustment, reduces the treatment cost, and reduces the secondary pollution of the environment.
Smart Images

Figure CN119553256A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sewage treatment, and particularly relates to an activated iron-based nanocrystalline alloy and application thereof in degrading phenol. Background Art
[0002] Coal chemical processes such as coal gasification and coking produce a large amount of wastewater. The pH value of wastewater produced by coal coking usually ranges from 7.7 to 11.5. This type of wastewater contains various organic and inorganic pollutants. Among them, phenols are one of the most important organic pollutants, and the phenol content can reach 4000-5000 mg / L. Phenol and its compounds have a strong toxic effect on living organisms and are difficult to degrade under natural conditions. The treatment methods for phenol-containing wastewater include three categories: physical, biological and chemical methods. Compared with physical and biological methods, chemical methods are widely used in the treatment of organic wastewater because they can degrade most organic pollutants indiscriminately and have the advantages of mild reaction conditions, simple equipment and efficient treatment. In particular, Fenton-like technology avoids the shortcomings of traditional Fenton technology, such as low effective utilization rate of hydrogen peroxide, large amount of catalyst addition, iron mud and secondary pollution. It is highly favored in the treatment of phenol wastewater. At the same time, iron-based nanocrystals are widely concerned due to their special properties.
[0003] Chinese patent application CN107326159B discloses a method and device for preparing and applying an iron-based nanocrystalline alloy for treating printing and dyeing wastewater containing azo dyes. The disclosed method is to obtain an iron-based nanocrystalline alloy strip by annealing an iron-based amorphous alloy strip, and further degrade the golden orange 2 dye. However, after annealing the 1K107BN85 strip at 800°C by this method, under the condition of a strip dosage of 10g / L, it still takes 10 to 15 minutes to degrade a 25mg / L golden orange 2 dye aqueous solution to reach a degradation rate of 90%; the patent mainly focuses on the method and device for preparing and applying an iron-based nanocrystalline alloy, and does not mention phenol, especially its degradation under neutral alkaline conditions.
[0004] In summary, the application of iron-based nanocrystalline alloys in phenol degradation is still in the exploratory stage. Summary of the invention
[0005] The purpose of the present invention is to provide an activated iron-based nanocrystalline alloy and its application in degrading phenol. The activated iron-based nanocrystalline alloy provided by the present invention can degrade phenol under neutral and alkaline conditions, breaking the limitation that Fenton-like reactions can usually only occur within a pH range of 2 to 5, reducing the need for pH adjustment during wastewater treatment and secondary pollution to the environment, reducing the treatment cost of phenol-containing wastewater, and facilitating wastewater treatment and environmental remediation.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing an activated iron-based nanocrystalline alloy, comprising the following steps:
[0008] The iron-based nanocrystalline alloy is immersed in a copper sulfate solution to activate the surface of the iron-based nanocrystalline alloy.
[0009] Preferably, the iron-based nanocrystalline alloy is an iron-based nanocrystalline strip.
[0010] Preferably, the concentration of the copper sulfate solution is 0.15 mol / L.
[0011] Preferably, the activation temperature is 20-80° C. and the activation time is 10-25 min.
[0012] The second technical solution of the present invention is to provide an activated iron-based nanocrystalline alloy prepared according to the preparation method of the activated iron-based nanocrystalline alloy.
[0013] The third technical solution of the present invention is to provide an application of the above-mentioned activated iron-based nanocrystalline alloy in the degradation of phenol.
[0014] Preferably, the step of degrading phenol comprises: adding hydrogen peroxide to water containing phenol, adjusting the pH value to 3-9, then adding the activated iron-based nanocrystalline alloy, stirring, and achieving degradation of phenol in the water.
[0015] More preferably, the degradation process is carried out at 25-65°C.
[0016] More preferably, the concentration of phenol in water is 5-300 mg / L; the concentration of H2O2 in water is 0.06-1 mol / L; the amount of the activated iron-based nanocrystalline alloy added is 0.1-15 g / L; the stirring speed is 50-1500 r / min, and the time is 1-12 min.
[0017] The present invention utilizes copper sulfate to activate iron-based nanocrystalline strips, and conducts catalytic degradation experiments under a Fenton-like system. The degradation efficiency is improved by more than 5 times compared with that of unactivated strips. By using 2 g / L of activated iron-based nanocrystalline strips, the phenol degradation rate can reach 95% in only 5 minutes under acidic and weakly acidic conditions.
[0018] Under neutral conditions, the unactivated iron-based nanocrystal strips have basically no degradation effect, while the activated iron-based nanocrystal strips can achieve a phenol degradation rate of 95% after a reaction time of 5 minutes; under alkaline conditions, when the pH is in the range of 7.5 to 9, the activated iron-based nanocrystal strips complete 95% phenol degradation in 12 minutes, while the unactivated iron-based nanocrystal strips have a degradation rate of only 20% in 30 minutes under alkaline conditions.
[0019] The activated iron-based nanocrystalline alloy provided by the invention has a high degradation efficiency for a phenol solution with a pH value of 3 to 9, thus broadening the application scope of the Fenton-like iron-based nanocrystalline alloy for degrading phenol.
[0020] The beneficial technical effects of the present invention are as follows:
[0021] The invention provides a method for broadening the application scope of phenol degradation by using copper sulfate to degrade iron-based nanocrystalline alloys. The method has the advantages of easy operation, low cost, simple process, high degradation efficiency, short required time, and the ability to degrade phenol under various environments.
[0022] Compared with other methods for degrading phenol, the raw material used in the present invention, namely industrial iron-based nanocrystalline alloy, is cheap and easy to obtain, and the effect of strengthening the iron-based nanocrystalline alloy in degrading phenol is significant and the cost is low.
[0023] The phenol degradation method provided by the invention is simple to operate, highly practical, and has a fast degradation rate, and is easy to promote and industrialize, and is of great significance for realizing water resource recycling, environmental governance, energy conservation, emission reduction, and sustainable development. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 The UV-visible absorption spectra of Example 1(a), Example 2(b), Example 3(c) and Example 4(d) at different time periods when degrading phenol.
[0025] Figure 2 The present invention is a curve showing the change of phenol concentration in phenol solution over time and the change of phenol degradation rate over time when phenol is degraded by activated iron-based nanocrystal strips in Examples 1 to 4, wherein (a) is a curve showing the change of phenol concentration in phenol solution over time when phenol is degraded by activated iron-based nanocrystal strips in Examples 1 to 3, (b) is a curve showing the change of phenol degradation rate over time when phenol is degraded by activated iron-based nanocrystal strips in Examples 1 to 3, (c) is a curve showing the change of phenol concentration in phenol solution over time when phenol is degraded by activated iron-based nanocrystal strips in Example 4, and (d) is a curve showing the change of phenol degradation rate over time when phenol is degraded by activated iron-based nanocrystal strips in Example 4.
[0026] Figure 3 The UV-visible absorption spectra of Comparative Example 1 (a), Comparative Example 2 (b) and Comparative Example 3 (c) at different time periods when phenol was degraded.
[0027] Figure 4 The curves (a) and (b) are the curves showing the change of phenol concentration in the phenol solution over time when phenol is degraded by iron-based nanocrystal strips in comparative examples 1 to 3 and the curves showing the change of phenol degradation rate over time. DETAILED DESCRIPTION
[0028] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0029] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0031] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0032] The grade of the iron-based nanocrystalline strips used in the embodiments and comparative examples of the present invention is 1K107.
[0033] Example 1
[0034] Activated iron-based nanocrystal ribbons for degradation of phenol:
[0035] Step (1), dissolving copper sulfate in deionized water to prepare a 0.15 mol / L copper sulfate solution;
[0036] Step (2), placing 1.0 g of 1K107 iron-based nanocrystal ribbon into 20 mL of the copper sulfate solution prepared in step (1), stirring magnetically (magnetic field strength 1 Tesla) to allow the ribbon to fully contact the copper sulfate solution, and placing it in an oven at 40° C. for 15 min for activation;
[0037] Step (3), taking out the activated iron-based nanocrystal strips and drying them in air for later use;
[0038] Step (4), taking 250 mL of 50 mg / L phenol solution into a 500 mL beaker, adding hydrogen peroxide to make the concentration of H2O2 in the solution 0.06 mol / L, adjusting the pH value to 3, and placing the beaker in a 65°C water bath;
[0039] Step (5), using 600r / min mechanical stirring to stir the phenol solution obtained in step (4), adding 0.5g of the activated iron-based nanocrystal strip obtained in step (3), and taking 0.25mL of the phenol solution into a centrifuge tube at 0.5min, 1min, 2min, 3min, 4min and 5min after adding the strip. Then, 0.05mL of ammonia-ammonium chloride buffer solution with a mass fraction of 20%, 0.1mL of 4-aminoantipyrine solution with a mass fraction of 2%, and 0.1mL of potassium ferricyanide solution with a mass fraction of 8% are added to the taken-out phenol solution in sequence for color development treatment, and after mixing evenly, deionized water is added to dilute to 3.5mL. Finally, the diluted sample solution is placed in a UV-visible spectrophotometer to measure its absorbance to determine the concentration of the phenol solution.
[0040] Example 2
[0041] Activated iron-based nanocrystal ribbons for degradation of phenol:
[0042] Compared with Example 1, the only difference is that in step (4), the pH value of the solution is adjusted to 7.
[0043] Example 3
[0044] Activated iron-based nanocrystal ribbons for degradation of phenol:
[0045] Compared with Example 1, the only difference is that step (4) adjusts the pH value of the solution to 9, and the sampling time of step (5) is 0.5 min, 1 min, 2 min, 3 min, 4 min, 5 min, 10 min, 11 min and 12 min.
[0046] Example 4
[0047] Activated iron-based nanocrystal ribbons for degradation of phenol:
[0048] Compared with Example 1, the differences are that 2.5 g of 1K107 iron-based nanocrystal strips are used in step (2), the beaker of the solution is placed in a 25° C. water bath in step (4), and the sampling time in step (5) is 1 min, 2 min, 3 min, 4 min, and 5 min.
[0049] The UV-visible absorption spectra of Example 1(a), Example 2(b), Example 3(c) and Example 4(d) at different time periods when phenol was degraded are shown in FIG. Figure 1 .
[0050] from Figure 1 As can be seen from (a), when pH = 3, phenol has been basically degraded after 0.5 min of reaction under the degradation condition, and its degradation rate is 98.25%.
[0051] from Figure 1As can be seen in (b), when pH = 7, the degradation rate of phenol under this degradation condition reaches 88.9% after 0.5 min; and the degradation rate reaches 97.6% after 5 min of degradation.
[0052] from Figure 1 As can be seen in (c), when pH = 9, the degradation rate of phenol is 37.5% after 5 minutes of degradation under the degradation condition; after 12 minutes of degradation, the degradation rate reaches 97.7%.
[0053] from Figure 1 As can be seen in (d), when pH = 3, phenol is degraded under this degradation condition after 1 minute, and its degradation rate is 93.38%.
[0054] Figure 2 The present invention is a curve showing the change of phenol concentration in phenol solution over time and the change of phenol degradation rate over time when phenol is degraded by activated iron-based nanocrystal strips in Examples 1 to 4, wherein (a) is a curve showing the change of phenol concentration in phenol solution over time when phenol is degraded by activated iron-based nanocrystal strips in Examples 1 to 3, (b) is a curve showing the change of phenol degradation rate over time when phenol is degraded by activated iron-based nanocrystal strips in Examples 1 to 3, (c) is a curve showing the change of phenol concentration in phenol solution over time when phenol is degraded by activated iron-based nanocrystal strips in Example 4, and (d) is a curve showing the change of phenol degradation rate over time when phenol is degraded by activated iron-based nanocrystal strips in Example 4.
[0055] Comparative Example 1
[0056] Degradation of phenol by iron-based nanocrystal strips:
[0057] Step (1), taking 250 mL of 50 mg / L phenol solution into a 500 mL beaker, adding hydrogen peroxide to make the concentration of H2O2 in the solution 0.06 mol / L, adjusting the pH value to 3, and placing the beaker in a 65°C water bath;
[0058] Step (2), using 600r / min mechanical stirring step (1) obtained phenol solution, adding 0.5g 1K107 iron-based nanocrystal strips, and taking 0.25mL of phenol solution into a centrifuge tube at 0.5min, 1min, 2min, 3min, 4min, 5min, 10min, 15min and 20min after adding the strips. Then, 0.05mL of ammonia-ammonium chloride buffer solution with a mass fraction of 20%, 0.1mL of 4-aminoantipyrine solution with a mass fraction of 2%, and 0.1mL of potassium ferricyanide solution with a mass fraction of 8% are added to the taken out phenol solution in sequence for color development treatment, and after mixing evenly, deionized water is added to dilute to 3.5mL. Finally, the diluted sample solution is placed in a UV-visible spectrophotometer to measure its absorbance to determine the concentration of the phenol solution.
[0059] Comparative Example 2
[0060] Degradation of phenol by iron-based nanocrystal strips:
[0061] Compared with Comparative Example 1, the only difference is that in step (1), the pH value of the solution is adjusted to 7, and the sampling time in step (2) is 10 min, 15 min, 20 min, 25 min, 30 min and 35 min.
[0062] Comparative Example 3
[0063] Degradation of phenol by iron-based nanocrystal strips:
[0064] Compared with Comparative Example 1, the only difference is that in step (1), the pH value of the solution is adjusted to 9, and the sampling time in step (2) is 10 min, 15 min, 20 min, 25 min and 30 min.
[0065] The UV-visible absorption spectra of Comparative Example 1 (a), Comparative Example 2 (b) and Comparative Example 3 (c) at different time periods when phenol is degraded are shown in FIG. Figure 3 .
[0066] from Figure 3 As can be seen in (a), when pH = 3, the degradation rate of phenol under this degradation condition is only 18.8% after 5 minutes of reaction, and the degradation rate reaches 98.8% after 20 minutes of degradation, indicating that the degradation rate of phenol by the iron-based nanocrystal strips that have not been strengthened by chemical activators is slow.
[0067] from Figure 3 As can be seen in (b), when pH = 7, phenol is basically not degraded under this degradation condition, and the degradation rate is only 10.8% after 35 minutes of reaction, indicating that the iron-based nanocrystalline strips that have not been strengthened by chemical activators basically do not degrade phenol under neutral conditions.
[0068] from Figure 3 As can be seen in (c), at pH = 9, the degradation rate of phenol under this degradation condition is only 6.6% after 10 minutes of reaction, and the degradation rate after 30 minutes of degradation is only 19.4%, indicating that the degradation degree of phenol by the iron-based nanocrystal strips not strengthened by chemical activators is low under alkaline conditions.
[0069] Figure 4 The curves (a) and (b) are the curves showing the change of phenol concentration in the phenol solution over time when phenol is degraded by iron-based nanocrystal strips in comparative examples 1 to 3 and the curves showing the change of phenol degradation rate over time.
[0070] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A method for preparing an activated iron-based nanocrystalline alloy, characterized in that: The following steps are involved: The iron-based nanocrystalline alloy is immersed in a copper sulfate solution to activate the surface of the iron-based nanocrystalline alloy.
2. The method for preparing an activated iron-based nanocrystalline alloy according to claim 1, characterized in that: The iron-based nanocrystalline alloy is an iron-based nanocrystalline strip.
3. The method for preparing an activated iron-based nanocrystalline alloy according to claim 1, characterized in that: The concentration of the copper sulfate solution is 0.15 mol / L.
4. The method for preparing an activated iron-based nanocrystalline alloy according to claim 1, characterized in that: The activation temperature is 20-80° C. and the activation time is 10-25 minutes.
5. The method for preparing an activated iron-based nanocrystalline alloy according to claim 4, characterized in that: The activation temperature is 30-60°C.
6. An activated iron-based nanocrystalline alloy obtained according to the method for preparing an activated iron-based nanocrystalline alloy according to any one of claims 1 to 5.
7. Use of the activated iron-based nanocrystalline alloy according to claim 6 in degrading phenol.
8. The use according to claim 7, characterized in that: The step of degrading phenol comprises: adding hydrogen peroxide to water containing phenol, adjusting the pH value to 3-9, then adding the activated iron-based nanocrystalline alloy, stirring, and realizing the degradation of phenol in the water.
9. The use according to claim 8, characterized in that: The degradation process takes place at 25-65°C.
10. The use according to claim 8, characterized in that: The concentration of phenol in water is 5-300 mg / L; the concentration of H2O2 in water is 0.06-1 mol / L; the amount of the activated iron-based nanocrystalline alloy added is 0.1-15 g / L; the stirring speed is 50-1500 r / min, and the time is 1-12 min.
Citation Information
Patent Citations
A method and apparatus for preparing and applying iron-based nanocrystalline alloys for treating dyeing and printing wastewater containing azo dyes.
CN107326159B